Cardiac arrest following an anaphylactic reaction to atracurium. (5th November 2010) - Miraj, Adilah; Foaud, Ahmad; Seth, Bharti
Abstract : This report describes a life-threatening anaphylactic reaction in a 58-year-old woman who was scheduled for subacromial decompression of right shoulder joint. She had a modified rapid sequence induction using fentanyl 100 µg, propofol 150 mg and suxamethonium 100 mg. Following induction her blood pressure and pulse were stable. On return of spontaneous ventilation, she had intravenous administration of 30 mg of atracurium. Soon after, she developed profound bradycardia followed by a cardiac arrest. Cardiopulmonary resuscitation (CPR) commenced with 100% oxygen and intravenous administration of atropine 3 mg and epinephrine 1 mg. After 1 min of CPR she had the return of spontaneous circulation with a blood pressure of 160/100 mm Hg. Her sedation was maintained using minimal isoflurane until the return of spontaneous ventilation to avoid awareness. Surgery was postponed. Later she made an uneventful recovery. Her serum tryptase level was raised and a positive intradermal reaction to atracurium confirmed atracurium anaphylaxis.